2016
DOI: 10.1002/tea.21344
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between secondary science teachers’ subject matter knowledge and knowledge of student conceptions while teaching evolution by natural selection

Abstract: The fundamental scientific concept of evolution occurring by natural selection is home to many deeply held alternative conceptions and considered difficult to teach. Science teachers’ subject matter knowledge (SMK) and the pedagogical content knowledge (PCK) component of knowledge of students’ conceptions (KOSC) can be valuable resources for helping students learn difficult science concepts such as natural selection. However, little research exists that explores the relationship between science teachers’ SMK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…other researchers as an indispensable prerequisite for good teaching (e.g., de Jong & van Driel, 2004;Gess-Newsome, 2015;Kind, 2009;Lucero, Petrosino, & Delgado, 2017;Nilsson & Loughran, 2012;Park & Oliver, 2008;van Driel & Berry, 2012). This is also the case for the second component "knowledge of instructional strategies" that "has been most frequently referred to in the literature as a main component of PCK" (Seung, Bryan, & Haugan, 2012, p. 453).…”
mentioning
confidence: 99%
“…other researchers as an indispensable prerequisite for good teaching (e.g., de Jong & van Driel, 2004;Gess-Newsome, 2015;Kind, 2009;Lucero, Petrosino, & Delgado, 2017;Nilsson & Loughran, 2012;Park & Oliver, 2008;van Driel & Berry, 2012). This is also the case for the second component "knowledge of instructional strategies" that "has been most frequently referred to in the literature as a main component of PCK" (Seung, Bryan, & Haugan, 2012, p. 453).…”
mentioning
confidence: 99%
“…In our review of these recent studies, we found few about teachers' misconceptions. Also, we found that researchers refer to students' or teachers' misconceptions frequently from a conceptual change perspective (Lucero et al, 2017; Potvin & Cyr, 2017). Although the latter approach is common, we found very few research articles about misconceptions connected to SMK or specialized knowledge for teaching (Huttner & Markman, 2016; Maerten‐Rivera et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 75%
“…Therefore, biology teachers must associate the origin of humankind with natural selection. This association importance for the teaching of evolution has been pointed out in several studies highlighting the need to find ways for it to be assimilated by students (Lucero et al 2017;Clarke-Midura et al 2018). Furthermore, the term "Australopithecus" refers to the ancient line of the genus Homo as described in several works such as Lovejoy (1981) and Leakey (1995).…”
Section: Data Collectionmentioning
confidence: 91%